MW heating of rock particles and their cross-dependencies. (September 2019) - Jokovic, Vladimir; Antonio, Christian; Morrison, Robert
Highlights: Microwave-infrared (MW/IR) sorting of minerals (ore particles). Magnetic and/or MW reactive particle has an impact on the heating of near-by particle. This cross-dependencies is highly likely to lead to miss-classification during the sorting process. The magnetic particles should be removed prior to MW/IR sorting. Abstract: Microwave heating inside a cavity is not uniform and depends on various factors such as: cavity geometry, properties of treated material and frequency. In most applications of microwave (MW) heating there is only a small variation in the nature of the feed. However, this is not the case for the MW/Infra-Red (IR) ore sorting. As microwaves are electromagnetic waves, the microwave field around a given ore particle is influenced by its dielectric and magnetic properties and the modified field should also influence the heating of neighbouring particles. While influence is reciprocal it is clear that particles with high dielectric properties will dominate field effects. Understanding of this process is important in the particle-by-particle ore sorting process where the accept/reject decision is based on the temperature of the ore particle. A series of experiments were conducted at the Julius Kruttschnitt Mineral Research Centre to investigate the impact of particle size and its (highly) electromagnetic properties upon the heating of other nearby particles. The results suggest that magnetic and/or MW responsive particles that are prone to heat strongly during MW heating will have an impact on the heating of neighbouring particles of intermediate responsiveness. The heating of particles which is influenced by other highly responsive particles is very likely to lead to misclassification during the sorting process.